2007
DOI: 10.2193/2005-702
|View full text |Cite
|
Sign up to set email alerts
|

Avian Community Structure Along a Mountain Big Sagebrush Successional Gradient

Abstract: We compared vegetative structure and bird communities among 4 successional states in central Oregon representing a continuum from 1) postburn grassland, 2) mountain big sagebrush—Idaho fescue (Artemisia tridentatA—Festuca idahoensis) shrub—steppe, 3) sagebrush—steppe—juniper (Juniperus occidentalis), to 4) old‐growth western juniper. Species richness, evenness, and diversity of bird communities were highest in old‐growth and mid‐successional juniper (22.9 species/transect and 23.6 species/transect, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
(23 reference statements)
2
30
0
Order By: Relevance
“…Our findings concur with breeding bird research from other rangeland systems that indicated bird community composition is dependent on variable patterns of fire and grazing (Knopf 1994, Skowno and Bond 2003, Krook et al 2007, Reinkensmeyer et al 2007, Gregory et al 2010). This makes intuitive sense when you consider the historical disturbance regime of grasslands and the affinity of grassland breeding birds to select areas with specific, varying levels of biomass (Knopf 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings concur with breeding bird research from other rangeland systems that indicated bird community composition is dependent on variable patterns of fire and grazing (Knopf 1994, Skowno and Bond 2003, Krook et al 2007, Reinkensmeyer et al 2007, Gregory et al 2010). This makes intuitive sense when you consider the historical disturbance regime of grasslands and the affinity of grassland breeding birds to select areas with specific, varying levels of biomass (Knopf 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Greater distances represented bird assemblages that were increasingly dissimilar to sagebrush bird communities and more representative of juniper woodlands (Balda and Masters 1980;Sedgwick 1987;Rosenstock and van Riper 2001;Reinkensmeyer et al 2007). The underlying gradient separating treatment points from the sagebrush bird community was a function primarily of competing sagebrush and piñon-juniper cover; decreased sagebrush and increased piñon-juniper cover resulted in greater ecological distances to the sagebrush bird community.…”
Section: Discussionmentioning
confidence: 99%
“…Biomass is one of the indirect indicators of age, density, successional stage, and productivity – important factors known to influence habitat selection and biodiversity [ Petranka et al , 1994; Sorensen and Fedigan , 2000; Reinkensmeyer et al , 2007; Martinuzzi et al , 2009b]. Recently, radar‐derived biomass has been used to improve species habitat models [ Bergen et al , 2007].…”
Section: Requirements For Vegetation Structure From Spaceborne Radar‐mentioning
confidence: 99%